On the Perfect Sphere: The Preference for Circular Compositions for Depicting the Universe in Medieval and Early Modern Art - Roger Ferrer-Ventosa (Religions, 2024)
This essay explores circular compositions in medieval and early modern art. Delving into the intersection of religious, philosophical, and scientific ideas, the text examines the prevalence of circular depictions in medieval and early modern aesthetics. Utilizing an interdisciplinary approach, the author draws from primary Hermetic and Neoplatonic sources, providing four reasons for this preference. Firstly, this essay explores the scientific understanding of the shape of the universe, planets, and stars. The second reason delves into the psychological, symbolic, and geometric aspects associated with circular compositions, connecting them to Christian cosmological diagrams and symbolism in the visual arts. Furthermore, the essay investigates the conceptualisation of the universe as a mirror reflecting the divine, emphasising the role of beauty in religious art. The essay concludes by examining the visual culture of medieval and early modern periods, tracing the evolution of circular representations from Roman coins and shields to illuminated manuscripts and paintings. The article sheds light on a hitherto underexplored aspect of medieval and early modern cultures, despite its significance in shaping symbolism and organizing iconographic programs within these periods.